1991
DOI: 10.1007/bf02190544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metoprolol on activity of β-adrenoceptor coupled to guanine nucleotide binding regulatory proteins in adriamycin-induced cardiotoxicity

Abstract: Prevention of cardiotoxicity without interfering with the therapeutic efficacy of adriamycin is a very crucial question. We have investigated the activity of beta-adrenoceptor coupled to guanine nucleotide binding regulatory proteins (G-proteins) and Ca(2+)-ATPase activity in experimental adriamycin-induced cardiotoxicity and the influence of metoprolol treatment on these variables. Adriamycin was administered to rats intravenously as a single dose of 6 mg/kg, and metoprol was continuously given by means of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
1
6
1
1
Order By: Relevance
“…We showed that Dox-treatment did not change Gsα protein expression, as it was reported in other study [8], [11], but increased forskolin response, suggesting an increase in AC expression and/or activity. This surprising data contrasts with other studies which reported a decreased AC activity [41], [42] or no change [43]. However, those differences seem to be due to the cardiotoxicity level since the Dox cumulative doses used were 24, 24.75 and 6 mg.kg −1 , respectively.…”
Section: Discussioncontrasting
confidence: 93%
“…We showed that Dox-treatment did not change Gsα protein expression, as it was reported in other study [8], [11], but increased forskolin response, suggesting an increase in AC expression and/or activity. This surprising data contrasts with other studies which reported a decreased AC activity [41], [42] or no change [43]. However, those differences seem to be due to the cardiotoxicity level since the Dox cumulative doses used were 24, 24.75 and 6 mg.kg −1 , respectively.…”
Section: Discussioncontrasting
confidence: 93%
“…This is also supported by the finding of a single transcript of Gi-a 2 of 2.35 Kb in the Northern blot ( fig. 2), in accordance with the reported size of Gi-a 2 messenger ribonucleic acid in cerebral cortex (Eriksson et al 1992a), heart (Fu et al 1991b & c) and olfactory tissues (Jones & Reed 1987).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the peptide we used corresponds to a sequence totally conserved in both humans and rats ( 15). Membrane proteins (75 Mg), prepared from normal rat ventricles as described ( 16), were subjected to electrophoresis on a 10% polyacrylamide gel in SDS and thereafter subjected to electrotransfer to nitrocellulose that was saturated with PMT buffer for 2 h at room temperature. The affinity-purified antibodies from patients and rabbits, and the mouse monoclonal antibody (mAb-35) ( 17) against calf brain muscarinic receptor used as a positive control, were incubated at 4°C overnight with the nitrocellulose strips.…”
Section: Methodsmentioning
confidence: 99%